Scelte linguistiche delle aziende svizzere nella comunicazione esterna e nella politica di assunzione in un contesto plurilingue - Casoni, Matteo (My University, 2015)
This contribution considers the presence and the choice of languages in Swiss companies' external communication (websites) and in their employment policy (job announcements). By means of quantitative data and a case study we highlight the relationship between languages and marketing practices. Our purpose is to identify the parameters (especially territorial) affecting the companies' communication strategies as well as to establish the position and the function of the national languages (in particular Italian, as a national and minority language) in a multilingual and globalized context. As a first result, we observe the tendency of companies (particularly in the industrial sector) to publish a multilingual website: German is the main language, English and French occupy similar positions. Italian is the fourth language. Even if less prominent, it does not seem to be threatened by other languages, though. A second result is that in job offers companies tend to request fewer languages than are actually required by the job, in order to guarantee a wider selection of candidates and to reduce the costs at this initial stage of the recruitment process.
Keywords: language practices; companies communication; languages of websites and in job announcements; Swiss multilingualism